Prevalence and Factors Associated with under-5 Mortality in Nigeria: Evidence from 2018 Nigeria Demographic and Health Survey - Ashis Talukder; Nusrat Jahan Sathi; Md. Akhtarul Islam; Sheikh Mohammed Shariful Islam; Iqramul Haq (Dr. Sulaiman Al Habib Medical Journal, 2021)
Under-five mortality is a substantial indicator of children’s health, well-being, and consequently, socioeconomic development of a country. The primary focus of this study was to estimate the prevalence and identify the factors associated with under-5 mortality in Nigeria. This research utilized the most recent data from the Nigeria Demographic and Health Survey (NDHS 2018), which is a nationally representative survey. We included all children within 59 months from their birth. Cox proportional hazard (PH) and Cox frailty models were applied to identify the factors associated with under-5 child mortality. A total of 33,924 under-5 children were included. The prevalence of under-5 death was 9.5% [95% Confidence Interval (CI): 9.2–9.8]. In the Cox frailty model at community level, the model reported that multiple births [Hazard Ratio (HR) = 3.0; 95% CI: 2.7–3.4], male children (HR = 1.2; 95% CI: 1.1–1.2), and small-size babies at birth (HR = 1.4; 95% CI: 1.2–1.5) were strongly associated with the high risk of under-5 mortality. Parents with lower education, children from lower wealth quantities, and shorter childbirth intervals similarly had higher hazards of under-5 mortality for both the Cox PH and Cox frailty models. Our results suggest that different health strategies for improving education, nutrition, and family planning might contribute to reduce under-5 mortality in Nigeria. The Nigerian Federal Ministry of Health and other agencies should consider to scale up health interventions to reduce under-5 mortality.